A new model for reinforced concrete columns strengthened with fibre-reinforced polymer. Issue 8 (22nd August 2020) - Isleem, Haytham F.; Wang, Zhenyu; Wang, Daiyu
Abstract : Much work has been published in recent years on the strength benefits of confining rectangular reinforced concrete columns less than 300 mm across and with an aspect ratio less than 3 with fibre-reinforced polymer wraps and anchors. However, there has been little published research on the effects of polymer confinement on larger, flatter columns. This paper provides a new strength-prediction model with a wider scope than those in the existing literature. Test results provided by two independent researchers for 44 specimens were used as a basis for the model expressions. The test database included columns with aspect ratios ranging from 1·5 to 4·0 and depths of section varying from 100 mm to 600 mm. The key parameters influencing the confined strength, including aspect ratio, number of polymer layers, hoop steel reinforcement and cross-sectional area, and configuration of polymer anchors, were all accounted for. For a sufficient amount of polymer confinement, the threshold values of the lightly and heavily confined columns were proposed to be 0·125 and 0·25, respectively. Finally, the accuracy of the proposed model was verified by comparing its predictions with the database, together with the predictions of other existing models.